2020
DOI: 10.1016/j.bpj.2020.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelins and ent-Sphingomyelins Form Homophilic Nano-Subdomains within Liquid Ordered Domains

Abstract: Sphingomyelin (SM), a major component of small domains (or lipid rafts) in mammalian cell membranes, forms a liquid-ordered phase in the presence of cholesterol (Cho). However, the nature of molecular interactions within the ordered SM/Cho phase remains elusive. We previously revealed that stearoyl-SM (SSM) and its enantiomer ( ent -SSM) separately form nano-subdomains within the liquid-ordered phase involving homophilic SSM-SSM and ent -SSM- ent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…When the F / F 0 ratios of POPC and PSM/Cho (1:1) were assumed to be the quenching rates in the disordered and ordered states, the L o /L d area ratio of POPC/PSM/Cho (1:1:1) was estimated to be 78:22. This ratio was comparable with the theoretical ratio of 76:24 obtained from the phase diagram of the POPC/PSM/Cho (1:1:1) membrane taking into account the reported area per lipid. The TEMPO quenching conditions optimized for the model membrane were applied to examine the ratio of the ordered areas on the exosome membranes. The F / F 0 ratios of both milk and PC3 exosomes were approximately 60%.…”
Section: Resultssupporting
confidence: 71%
“…When the F / F 0 ratios of POPC and PSM/Cho (1:1) were assumed to be the quenching rates in the disordered and ordered states, the L o /L d area ratio of POPC/PSM/Cho (1:1:1) was estimated to be 78:22. This ratio was comparable with the theoretical ratio of 76:24 obtained from the phase diagram of the POPC/PSM/Cho (1:1:1) membrane taking into account the reported area per lipid. The TEMPO quenching conditions optimized for the model membrane were applied to examine the ratio of the ordered areas on the exosome membranes. The F / F 0 ratios of both milk and PC3 exosomes were approximately 60%.…”
Section: Resultssupporting
confidence: 71%
“…The liquid ordered state is characterized by a high level of order but relatively fast lateral diffusion. Recent studies indicate that the liquid ordered state is composed of gel/solid-like phospholipid or sphingolipid subdomains laterally separated by sterol-rich layers [32,33]. An analogy to the liquid ordered state would be a cluster of small icebergs separated by a thin layer of liquid so that they can laterally diffuse rapidly within the cluster relative to each other despite having a solid internal state.…”
Section: Membrane Physical State and Domain Formationmentioning
confidence: 99%
“…The sizes of the observed ND were in the range of 5-60 nm. In particular, Yano et al [34] examined the details of their formation by stearoyl-SMs (SSMs) using FRET measurements in lipid bilayers containing SSM and its enantiomer (ent-SSM), dioleoyl-phosphatidylcholine (DOPC), and Chol. In contrast to the uniform domains seen by microscopy, FRET analysis using fluorescent donor-and acceptor-labeled SSM showed distinct differences in SM and ent-SM colocalization within nanoscale distances.…”
Section: Model Lipid Membranesmentioning
confidence: 99%
“…Often, a kind of "stimulator" of the formation of NDs is Chol. In particular, Yano et al showed [34] that in mixtures with SM, Chol enhances the formation of H-bonds between SM molecules, limiting the conformational mobility of their acyl chains in the nonpolar region of the bilayer [70,71]. In turn, this contributes to the formation of NDs inside the L o phase of the membrane.…”
Section: Role Of H-bonds In Formation Of Ndsmentioning
confidence: 99%